The Concept of Ibnu Miskawaih Moral Education For Students - Zainuddin Zainuddin (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2021)
Although both education and morality are different, in practice they are closely related and synergistic. In the Islamic world, even education is in a lower dimension than morality. This shows that the importance of morality is so important that knowledge seems to fade away its essence without morality. Ibn Miskawaih is a thinker who is concerned with the moral dimension. The idea of morals boils down to divine values and Islamic ethics. Ibn Miskawaih offers his character concept emphasizing psychological and religious aspects to improve the character quality of students. This research is a literature study with a descriptive text analysis method. The results showed that Ibn Miskawaih was very intense in applying the habit method to explore the character of students. According to Ibnu Miskawaih, environmental habits, friends and family are the most important media in educational media